Enhancing Market Openness through Regulatory Reform in the People's Republic of China - Greene, Malory (OECD Trade Policy Papers, 2008)
This study analyses the People's Republic of China's trade policy environment with a focus on trade-related regulations and their role in supporting China's market openness. It examines in particular to what extent China's trade regulations comply with the principles of transparency and non-discrimination and facilitate foreign trade operations and international competition. The report proposes a series of policy recommendations to make China's regulatory framework more market-oriented and trade-and-investment friendly. The study is complemented with a business survey of OECD member country enterprises and Chinese firms. The survey assesses government influence on the investment climate through the impact of their policies on the costs, risks and barriers to competition facing firms. The main report and the business survey conclude that transparency plays a critical role in the development of a healthy business environment by reducing regulatory impediments